Evaluation of Haematological parameters in Katjang and Boer Goats (in different time periods) - Nur Atiqah Roshidi (2016)
This study was conducted in the Faculty of Sustainable Agriculture (FSA), Universiti Malaysia Sabah (UMS) to study the haematological parameters between the local Katjang and Boer crossbreed goats. The aim of this study was also to compare the effect of haematological arameters of the goats at different time periods. A total number of twenty female goats were used in this study and divided into two breeds which were [Katjang (n= 10) and Boer (n= 10)]. Blood samples were collected in the morning (6 -S a.m.), afternoon (12 noon - 2 p.m.) and evening (4 - 6 p.m.). The blood samples were analysed for haematological parameters using Auto Haematology Analyzer. For each period, ambient temperature and relative humidity were recorded by means of a data logger. The results obtained for Katjang goats In this study showed that there was no significant difference (p>0.05) of all haematological parameters at different time periods except for the composition of MCHC (29S.63±10.4S) which showed a Significant different (p<0.05). On the other hand, the result obtained for Boer goats In this study showed that there was no Significant difference (p>0.05) of haematological parameters in the effect of three different time periods. In the effect of breed factor, this study resulted that the mean ± standard deviation of all haematological parameters in Katjang goats which were RBC (15.27±2.42), HGB (7.S0±1.50), HCT (26.02±4.73), MCV (17.03±1.11), MCH (5.06±0.29), MCHC (299.1±10.86) and ROW (20.21± 0.97) were in a normal range except WBC (16.16 ± 4.86) which were out of normal ranges. In Boer goats, the mean ± standard deviation of RBC (17.20±2.9O), HGB (9.29 ±1.10), HCT (29.38±4.36), MCV (17.23±2.10), MCH (5.47±0.45), MCHC (319.5±16.84) and ROW (20.50 ±1.79) also showed the normal range except for WBC that exceed the standard ranges which was 17.85 ± 5.26 respectively. This study also revealed that breed between local Katjang and crossbreed Boer had significantly influenced (p<0.05) on some of haematological parameters which were HGB (8.55± 1.29), MCH (5.27± 0.37) and MCHC (309.3±l3.S5). Haematological values for this study could serve as baseline information for comparison in physiology and health status of farm animals. It can be conduded that environmental factors and breeds had significant changes on some haematological parameters of goats.